559 Ideation Jams: Catalyzing Interdisciplinary Teams to Maximize Research Impact - Elizabeth LaPensee; Barabara Salem; Jane Bugden; Mark Cantrell; Maureen Brudzinski March; Elias Samuels; Emily Somers (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: There is broad recognition that interdisciplinary research teams are uniquely suited to address complex research questions. At the Michigan Institute for Clinical & Health Research, we recognized a significant gap in support services at the University of Michigan for coordinating interdisciplinary teams to advance translational research. METHODS/STUDY POPULATION: The initial team science challenge we tackled was how to bring together cross-disciplinary groups, for the first time, to engage meaningfully and collaboratively with a ‘wicked’ problem of interest and create a shared vision. To address this, we developed Ideation Jams, which are facilitated experiences that help new groups build community, identify and prioritize research opportunities, determine how individual interests and other potential partners align with opportunities, and commit to next steps that will advance collaborative efforts. Ideation Jams leverage the methods and mindsets of design thinking, including divergence and convergence; making information visual; amplifying diversity; horizontal distribution of responsibility; and bias towards action. RESULTS/ANTICIPATED RESULTS: We have facilitated 11 Ideation Jams with 255 participants, including faculty, staff, health practitioners, and community members, who brought diverse expertise and insight to the research problems. Participant feedback has been overwhelmingly positive, with Ideation Jams fostering shared vision and innovation, and positively impacting various measures related to team performance. Participants have reported that Ideation Jams catalyzed various outcomes, including submission and award of grants, the introduction of new and specialized clinical offerings, and development of an interdisciplinary research agenda for their field of interest. Most recently, we trained representatives from five Clinical & Translational Science Award hubs to implement Ideation Jams at their universities. DISCUSSION/SIGNIFICANCE: Ideation Jams are ideal for mobilizing new groups around complex research problems, moving them from blue-sky thinking to action planning in three hours. Ideation Jams will be integrated into a suite of facilitated experiences, trainings, and grant development services to provide iterative support as teams advance their research priorities.